Ectopic pregnancy: an observational study in a tertiary care centre of Southern Rajasthan, India - Parmar, Shrusti; Sharma, Nalini; Dhakar, Vimla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: One among the three chief obstetric causes of bleeding in first trimester, ectopic pregnancy is the first thing to rule out as a gestation is suspected. The present study observes and analyses sociodemographic distribution, risk factors, presentation, diagnosis and treatment modalities in a tertiary care centre. Methods: An observational cross-sectional study, conducted among patients who were diagnosed and managed in department of obstetrics and gynaecology of a tertiary care centre. Data analyzed and explained as frequency, percentage, mean and standard deviation. Results: Age group between 21 to 30 years (69.9%) and multigravida (68.5%) are high risk for ectopic pregnancy (EP). Menstrual history was regular in 86.3%. Risk factors identified were previous abortion (30%) and history of pelvic inflammatory disease (30%). In 80.9% pain in abdomen was presenting complaints followed by bleeding per vaginum (60%), amenorrhoea (60%) and nausea and vomiting (32.9%). Right salpingectomy was most common in 43.8%, followed by left salpingectomy in 28.8%, methotrexate in 15.1%, left salpingo-ophorectomy in 5.5%, right salpingo-opherectomy in 5.5% and removal of tubal abortion in 1.3% patients. Laparoscopy was chosen route in majority 64.4% patients. Conclusions: Ectopic pregnancy - a gynecological catastrophe as well as a major challenge to the reproductive performance of women worldwide, should be considered a relevant public health issue. By providing adequate materials, manpower, well-equipped health facilities as well as a prompt and efficient referral system, good access roads and efficient transportation, will ensure early presentation in hospitals and prompt management of cases.